2018
DOI: 10.1002/hyp.13346
|View full text |Cite
|
Sign up to set email alerts
|

Water mining from the deep critical zone by apple trees growing on loess

Abstract: There have been significant recent advances in understanding the ecohydrology of deep soil. However, the links between root development and water usage in the deep critical zone remains poorly understood. To clarify the interaction between water use and root development in deep soil, we investigated soil water and root profiles beyond maximum rooting depth in five apple orchards planted on farmland with stand ages of 8, 11, 15, 18, and 22 years in a subhumid region on the Chinese Loess Plateau. Apple trees roo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
76
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 117 publications
(86 citation statements)
references
References 40 publications
8
76
1
1
Order By: Relevance
“…Our group has already performed many observations to clarify how apple trees use water in deep soil, and therefore how this affects groundwater recharge. These studies found a continuous decrease in soil water content in deep soil following afforestation [19,44], and the decreased soil water content in deep soil prevent groundwater recharge [34,45]. In this study, we first synthesize our previous published and newly collected soil water profiles to enrich our understanding of apple trees' water use in deep soil, and then investigate the water recovery process by measuring soil water profiles in deforested apple orchards with different ages.…”
Section: Soil Sampling and Analysismentioning
confidence: 99%
See 4 more Smart Citations
“…Our group has already performed many observations to clarify how apple trees use water in deep soil, and therefore how this affects groundwater recharge. These studies found a continuous decrease in soil water content in deep soil following afforestation [19,44], and the decreased soil water content in deep soil prevent groundwater recharge [34,45]. In this study, we first synthesize our previous published and newly collected soil water profiles to enrich our understanding of apple trees' water use in deep soil, and then investigate the water recovery process by measuring soil water profiles in deforested apple orchards with different ages.…”
Section: Soil Sampling and Analysismentioning
confidence: 99%
“…Twelve paired-plot sites were sampled in May 2014, with each site thus containing a standing apple orchard and an adjacent cropland. The apple orchard ages were 5,8,11,12,17,18,19,19,20,22,24 and 26 years at the 12 different sites. Here, the annual cropland serves as the control site to study how soil water is depleted due to growing apple trees relative to the annual cropland.…”
Section: Soil Sampling and Analysismentioning
confidence: 99%
See 3 more Smart Citations